Exploring Usability, Practicality, and Innovation of Flipbook-Based Interactive E-Books in Physics Education - Marisda, Dewi Hikmah; Tolla, Ismail; Arsyad, Muhammad; Arismunandar, Arismunandar (Journal of Innovation in Educational and Cultural Research, 2025)
Based on the development of digital technology in education, this study aims to explore the practicality of modern physics e-books based on interactive flipbooks in supporting student learning. This study focuses on improving the accessibility, interactivity, and readability of complex modern physics materials. The methodology used is research and development (RD) with an evaluative approach involving prospective physics teacher students and lecturers. The study results show that this e-book has a high level of practicality, with the majority of criteria scoring above 80%. A broad-scale practicality evaluation showed that the feedback and assessment features had the highest level of practicality (96.53%), followed by visual design and aesthetics (95.83%). Lecturers' responses also showed positive results, averaging 91.67%, although the visual appeal aspect still needs improvement. The main contribution of this study is to provide an innovative model for the development of interactive digital teaching materials based on flipbooks, as well as insights for developing a technology-based physics education curriculum. With the improvement of AI-based adaptive features and integration with the Learning Management System (LMS), this e-book has the potential to be a more effective and personalized digital learning solution in the digital era.